Ferguson and the death of Michael Brown on Twitter: #BlackLivesMatter, #TCOT, and the evolution of collective identities. Issue 11 (2nd September 2017) - Ray, Rashawn; Brown, Melissa; Fraistat, Neil; Summers, Edward
ABSTRACT: Recent events related to police brutality and the evolution of #BlackLivesMatter provides an empirical case to explore the vitality of social media data for social movements and the evolution of collective identities. Social media data provide a portal into how organizing and communicating generate narratives that survive over time. We analyse 31.65 million tweets about Ferguson across four meaningful time periods: the death of Michael Brown, the non-indictment of police officer Darren Wilson, the Department of Justice report on Ferguson, and the one year aftermath of Brown's death. Our analysis shows that #BlackLivesMatter evolved in concert with protests opposing police brutality occurring on the ground. We also show how #TCOT (Top Conservatives on Twitter) has operated as the primary counter narrative to #BlackLivesMatter. We conclude by discussing the implications our research has for the #BlackLivesMatter movement and increased political polarization following the election of Donald Trump.